PERCUTANEOUS TREATMENT OF BENIGN BILIARY STRICTURES AND BILIARY MANOMETRIC PERFUSION TEST - Thomas, Rohit Philip; Köcher, Martin (Biomedical papers, 2007)
Background: Benign biliary strictures are usually treated surgically or endoscopically. When these strictures are not accessible by endoscope or when open repair is not possible, percutaneous dilatation treatment is indicated. The efficacy of treatment is usually evaluated by clinical trial which includes leaving a small non-functional catheter in situ and following liver function tests. The evaluation may be effectively done by the biliary manometric perfusion test.Aim: The aim of this paper is to emphasize the importance of percutaneous dilatation treatment of benign biliary strictures with focus on the role of the biliary manometric perfusion test and its future prospects.Methods and Results: Based on the literature and our own experience, this article gives a short overview of percutaneous treatment of benign biliary strictures, indications, techniques, complications and results. The treatment of these strictures has an overall success rate between 60 to 90 %. This article also explains the biliary manometric test, the technique and its importance in evaluation of treatment success.Conclusion: Benign biliary strictures of the hepatic duct junction or bilio-enteric anastomosis are difficult to treat surgically and are endoscopically inaccessible. Percutaneous treatment by balloon dilatation and long term externalinternal drainage is feasible in the majority of these patients. It is minimally invasive, safe and effective. The evaluation of the treatment success may be more effectively done by the manometric perfusion test. It is easy, reliable, less time-consuming giving immediate results, and relatively safe.
Keywords: Benign strictures/Biliary tract/Balloon dilatation/Percutaneous transhepatic drainage/Manometric test